ADDITIONAL PROBIOTIC SACCHAROMYCES SPP. (YEAST CULTURE) IN RATING ON CARCASS OF LANDRACE CROSSING PIGS - N. W. E., Setyawati; Bidura, I G. N. G.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika; Vol 10 No 3 (2022): Vol. 10 No. 3 Tahun 2022; September - December, 2022)
This study aims to determine the effect of the addition of probiotic Saccharomyces spp. (tape yeast) on cross breed Landrace pig carcasses. This study was conducted at Banjar Kamasan, Dajan Peken Village, Tabanan District, Tabanan Regency and lasts for approximately three months. The Studi used was a completely randomized design (CRD) consisting of 4 treatments, namely P0: cross breed Landrace pigs fed a diet without Saccharomyces spp. probiotics. (yeast culture) as a control, P1: Cross breed Landrace pigs fed a diet with the probiotic Saccharomyces spp. (yeast culture) 0.1%, P2: Cross breed Landrace pigs fed with probiotic Saccharomyces spp. rations. (yeast culture) by 0.2%, P3: Cross breed Landrace pigs fed a diet with the probiotic Saccharomyces spp. (yeast culture) by 0.3%. Each treatment had 4 replications. The variables observed were slaughter weight, carcass weight, carcases percentage and protein consumption. The results showed that the administration of probiotic Saccharomyces spp. (tape yeast) 0.3% (P3) was the treatment with the highest slaughter weight, carcass weight, carcass percentage and protein consumption compared to other treatments, namely 74.35 kg/oak, 52.73 kg/oak, 71, 06% and 21,525.61 g/oak and were statistically significantly different (P<0.05). Based on this study it can be concluded that the administration of probiotic Saccharomyces spp. (tape yeast) given to cross breed Landrace pigs can increase slaughter weight, carcass weight, carcass percentage and protein consumption. Provision of probiotic Saccharomyces spp. (tape yeast) of 0.3% is the best treatment result. Keyword: Saccharomyces spp. (yeast culture), probiotic, carcases, cross breed Landrace pig